Banana seed genetic resources for food security: Status, constraints, and future priorities - Kallow, Simon; Mertens, Arne; Janssens, Steven, B.; Vandelook, Filip; Dickie, John; Swennen, Rony L.; Panis, Bartholomeus (Wiley, 2022)
Storing seed collections of crop wild relatives, wild plant taxa genetically related to crops, is an essential component in global food security. Seed banking protects genetic resources from degradation and extinction and provides material for use by breeders. Despite being among the most important crops in the world, banana and plantain crop wild relatives are largely under-represented in genebanks.